Trauma across the life course and pathways to healing for older women experiencing homelessness - Wenzel, Suzanne L. (Frontiers in Global Women's Health, 2025)
Older women are increasingly experiencing the trauma of homelessness. The precipitants and concomitants of homelessness are also traumas, are multifold, and reflect women's intersectional identities and experiences over their life course. Older women with experiences of homelessness and other traumas require pathways to healing, a life they experience as full and valued. Housing is a necessary and non-negotiable ingredient in addressing the well-being of older women with experiences of homelessness and other traumas. Research indicates that housing alone is not sufficient to achieve healing from homelessness and other traumas; rather, the combination of Permanent Supportive Housing (PSH) and Trauma-Informed Care (TIC) is essential and foundational. Promising approaches to support healing are examined and proposed as future directions to complement the foundation of PSH and TIC. Multiple structural inequities underlying older women's homelessness must also be addressed through policy action. The need for a fundamental shift in how we, as a society, regard and implement public assistance to combat homelessness is discussed in the context of the “Duty-to-Assist” framework.